The Cognitive Behavioral Therapy Reduces Depression in Chronic Kidney Disease Patients Undergoing Hemodialysis - Yunani Sri Astuti; Tantri Widyarti Utami (Indonesian Journal of Global Health Research, 2021)
Chronic kidney disease is a global health problem with increased prevalence and incidence of kidney disease, poor prognosis, and high cost. Psychological problems occur, one of which is depression. Various interventions are needed to reduce depression including Cognitive behavioral therapy. The aim is to determine the effectiveness of cognitive-behavioral therapy on depression in chronic kidney disease patients. This is a quasi-experimental pre-post test with a control group with cognitive behavioral therapy intervention. A total is 40 patients with chronic kidney disease undergoing hemodialysis and experiencing depression in two hospitals in Bogor were included in the study during the period from March 2020 to December 2020. The data analysis used is the Wilcoxon test and Man U Whitney test. The results have shown that depression decreased in patients with chronic kidney disease after cognitive behavioral therapy (p-value= 0,036). These results suggest that cognitive-behavioral therapy is a promising intervention for treating depression in chronic kidney disease patients.